Patient-Derived Xenograft: A More Standard “Avatar” Model in Preclinical Studies of Gastric Cancer - Zeng, Mingtang; Pi, Chao; Li, Ke; Sheng, Lin; Zuo, Ying; Yuan, Jiyuan; Zou, Yonggen; Zhang, Xiaomei; Zhao, Wenmei; Lee, Robert J.; Wei, Yumeng; Zhao, Ling (Frontiers in Oncology, 2022)
Despite advances in diagnosis and treatment, gastric cancer remains the third most common cause of cancer-related death in humans. The establishment of relevant animal models of gastric cancer is critical for further research. Due to the complexity of the tumor microenvironment and the genetic heterogeneity of gastric cancer, the commonly used preclinical animal models fail to adequately represent clinically relevant models of gastric cancer. However, patient-derived models are able to replicate as much of the original inter-tumoral and intra-tumoral heterogeneity of gastric cancer as possible, reflecting the cellular interactions of the tumor microenvironment. In addition to implanting patient tissues or primary cells into immunodeficient mouse hosts for culture, the advent of alternative hosts such as humanized mouse hosts, zebrafish hosts, and in vitro culture modalities has also facilitated the advancement of gastric cancer research. This review highlights the current status, characteristics, interfering factors, and applications of patient-derived models that have emerged as more valuable preclinical tools for studying the progression and metastasis of gastric cancer.